Unlocking Africa’s agricultural potential - Roseboom, Johannes; Beintema, Nienke M.; Lynam, John K.; Badiane, Ousmane (International Food Policy Research Institute, 2016)
The preceding chapters of this volume have covered the spectrum of challenges facing Africa south of the Sahara (SSA) in its efforts to develop an effective and efficient agricultural research and development (R&D) system at national, subregional, and regional levels. This chapter endeavors to synthesize the key messages of the individual chapters in order to present an overview of the actions required to unlock the inherent potential of agricultural R&D in the quest for faster growth and more broadly shared development outcomes. The discussion begins with a summary of why resolving the issue of underinvestment in agricultural R&D is fundamental to advancing the region’s technical progress and, hence, raising agricultural productivity. Next, the case is made for the essential need to develop rural innovation capacity to motivate the adoption of new technologies by farmers and increase farm productivity. Finally, the chapter presents the key strategies needed to address current limitations and inefficiencies in agricultural R&D financing, human resources, organization and management, and systems-level structuring.